A Study on Students' Motivation and Its Correlation with English Reading Comprehension Achievement at sky- line lower-secondary school, Da Nang city - Nguyễn Thị Hồng Nhung (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to examine the motivation of students at Sky-line secondary school in Da Nang, Vietnam, specifically their engagement with different types of English texts. It seeks to identifyfactors influencing their motivation to read in English and explore any correlation between reading motivation and overall reading 2 achievement. The study also aims to provide recommendations forenhancing Vietnamese learners' motivation to read in English, based on the research findings. By addressing these objectives, the study aims to contribute to the field of English language education and support the development of effective strategies for promoting reading motivation among students at Sky-line secondary school.